PREVALENCE AND COPING STRATEGIES OF DYSMENORRHEA AMONG UNDERGRADUATE NON-MEDICAL STUDENTS - MUGHAL, AS; BIBI, A; ASHIQ, H; SALMAN, S; GULZAR, Z; QAMAR, S; MUSTAFA, AL; TARIQ, S (Biological and Clinical Sciences Research Journal, 2023)
Although dysmenorrhea is not a life-threatening disorder, it can have a significant negative impact on both individuals and society. Dysmenorrhea is a chronic condition that causes significant pain, cramping, and constriction in the lower abdomen. Additional symptoms like sweating, headaches, nausea, vomiting, and diarrhea frequently accompany it. Primary dysmenorrhea is another pain term with no obvious medically identifiable gynecological etiology. This study conducted a cross-sectional investigation on a sample of 377 people gathered from various women's colleges in Karachi. Version 24 of SPSS was utilized for the analysis. The results show that the participants knew about the risk factors of dysmenorrhea, but knowledge regarding dietary recommendations and physical activity was low. This study provides insight into the incidence of dysmenorrhea among undergraduate non-medical females and the coping strategies used by these students. This information will benefit medical care providers to recommend the most effective strategies according to medical literature to those not using the effective method. A program of awareness development is required to promote young females' health.